Tolerance of Perovskite Solar Cell to High-Energy Particle Irradiations in Space Environment - Miyazawa, Yu; Ikegami, Masashi; Chen, Hsin-Wei; Ohshima, Takeshi; Imaizumi, Mitsuru; Hirose, Kazuyuki; Miyasaka, Tsutomu (iScience, 2018)
Materials to be used in the space environment have to withstand extreme conditions, particularly with respect to cosmic particle irradiation. We report robust stability and high tolerance of organolead trihalide perovskite solar cells against high-fluence electron and proton beams. We found that methylammonium and formamidinium-based lead iodide perovskite solar cells composed of TiO2 and a conductive polymer, as electron and hole transport materials, can survive against accumulated dose levels up to 1016 and 1015particles/cm2 of electrons (1 MeV) and protons (50 KeV), respectively, which are known to completely destroy crystalline Si-, GaAS-, and InGaP/GaAs-based solar cells in spacecraft. These results justify the superior tolerance of perovskite photovoltaic materials to severe space radiations and their usefulness in satellite missions. [Display omitted] •Lead halide perovskites have extreme stability against electron and proton irradiations•Radiation tolerance of perovskite solar cells can exceed those of Si- and GaAs-based cells•Proton beam focused to perovskite absorber revealed high stability up to 1014 protons/cm2•Our study shows the usefulness of lightweight perovskite solar cells in satellite missions Aerospace Engineering; Energy Materials; Materials Structure.